Population structure and maturity stages of Fritillaria borealis (Appendicularia, Tunicata): seasonal cycle in Ushuaia Bay (Beagle Channel) - Hoffmeyer, Monica Susana; Presta, María Laura; Capitanio, Fabiana Lia (Brazilian Journal of Oceanography)
Fritillaria borealis is a cosmopolitan species, veryfrequent in sub-antarctic and antarctic waters. Theobjective of this paper was to analyze its size structureand maturity stages at two sites in Ushuaia Bay:a coastal site exposed to anthropogenic pressure (E1)and a reference site (E2) located in the external zoneof the bay. Zooplankton was collected during the2012 seasonal cycle. The sampling method involvedthe use of a 67 μm-mesh net. Appendicularianswere classified in four maturity stages: I) undifferentiatedgonads, II) testis and ovary differentiated,III) expanded testis, IV) discharged testis, expandedovary. Our results showed that the highest densitiesof F. borealis occurred in spring and summer at bothsites; coinciding with high values of chlorophyll-a.The percentage of juveniles (I and II) exhibited aspatial and temporal pattern similar to that observedfor chlorophyll-a values. During spring-summer,juveniles and mature specimens (III and IV) showeda greater gonadal development than those individualsfound in autumn-winter. In conclusion, themismatching in the population structure and the patternof densities of F. borealis between coastal andexternal zones would suggest the existence of twosub-populations susceptible to the influence of theanthropogenic impact in the bay. Fritillaria borealis é uma espécie cosmopolita, muito frequente em águas subantárticas e antárticas. O objetivo do trabalho foi analisar a estrutura de tamanhos e estádios de maturação da espécie em dois locais da Bahía Ushuaia: um costeiro, sujeito à pressão humana (E1), e um local de referência (E2) na zona externa da baia. O zooplâncton foi coletado no ciclo sazonal 2012. O método de amostragem envolveu o uso de uma rede de 67 micrômetros de abertura de malha. As apendiculárias foram classificadas em quatro estádios de maturação: I) gônada indiferenciada, II) testículo e ovário diferenciados, III) testículo expandido, IV) testículo descarregado, ovário expandido. Nossos resultados mostraram que as maiores densidades de F. borealis ...